Flexing as a Marketing Strategy: A Perspective from Islamic Economic Law - Sa'diyah, Siti; Rizka, Rizka; Rosyadi, Imron (Universitas Muhammadiyah Sidoarjo, 2024)
This research aims to analyze flexing in marketing from the perspective of Shariah economic law. The phenomenon of flexing, as a common marketing strategy, has recently become prevalent, particularly on social media. However, the current development of flexing presents several issues as it tends to disregard Shariah concepts, thereby potentially harming consumers. This study is a literature review that utilizes primary sources, such as interpretations by Yusuf Qardhawi and economist Reynal Kasali through YouTube channels, as well as secondary sources, including the phenomenon of flexing on social media. The findings of this research indicate that flexing can support marketing activities but tends to have negative impacts on society. Therefore, Islamic business practitioners are advised against employing flexing as a marketing tool, as it violates Shariah principles, such as avoiding defamation, arrogance, ostentation, extravagance, and hypocrisy.